FAMILY AND SCHOOL COOPERATE CLOSELY - SUCCESS IS GUARANTEED - Abdrashitova E. V. (Galaxy International Interdisciplinary Research Journal, 2022)
Unfortunately, the modern school system is far from perfect. Even at school, children have to master a lot of material on their own, the program is held at an accelerated pace. It is impossible to do without the help of classical old and modern teaching methods. It is necessary to motivate the student to search for additional information. To teach to find and navigate independently in the information received, to form creative thinking, to develop natural abilities using the latest achievements of science and technological techniques.